Prevalencia de la desnutrición en niños menores de 5 años del Centro de Salud Siete de Octubre del cantón Quevedo, 2014 - Sanclemente Carbo, Gina Carola (2015)
The prevalence of malnutrition remains a significant problem throughout the world, particularly among children under five years, the malnutrition reaches affect the linear growth (chronic malnutrition), due to different factors such as low birth weight of a mother with gestational malnutrition, duration of exclusive breastfeeding, early weaning, as well as the incidence of contagious diseases such as acute diarrheal disease, acute respiratory infection and anemia in children.The objective of the research to determine the prevalence of malnutrition in children less than five years attending the health center October 7 of the canton Quevedo. Where they proceededto compilation of information to all the mothers of children who had some degree of malnutrition, regardless of the type of malnutrition that presented the child. It was a descriptive cross-sectional study of non-invasive type, the research method is a non-experimental qualitative-quantitative. The results highlighted that we allowed to know what type of malnutrition presented the study group were, with a 36.98 %, with chronic malnutrition, unlike the global malnutrition with the 17.80 %. The incidence of diseases such as acute respiratory infection with the 56.60 %. The presence of anemia both mild and moderate with the 93.16 % and with a low consumption of iron supplements with the 54.80 %. KEY WORDS: chronic malnutrition, prevalence, children, anemia. Protective factors.